2010
DOI: 10.1126/science.1195481
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Germline Genes Drives Malignant Brain Tumor Growth in Drosophila

Abstract: Model organisms such as the fruit fly Drosophila melanogaster can help to elucidate the molecular basis of complex diseases such as cancer. Mutations in the Drosophila gene lethal (3) malignant brain tumor cause malignant growth in the larval brain. Here we show that l(3)mbt tumors exhibited a soma-to-germline transformation through the ectopic expression of genes normally required for germline stemness, fitness, or longevity. Orthologs of some of these genes were also expressed in human somatic tumors. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
329
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(342 citation statements)
references
References 34 publications
12
329
0
Order By: Relevance
“…It is noteworthy that the GFP::Piwi protein observed in mip130 1-36 salivary glands is cytoplasmic, whereas native piwi requires translocation into the nucleus to be functional (46), suggesting that the observed expression is not coordinately controlled with other genes required for piwi transport to the nucleus and function in that compartment. Janic et al (11) reported that piwi and other germ-line genes generally repressed in somatic tissues are activated in malignant brain tumor tissue in l(3)mbt mutants. We asked if mip130 1-36 mutation would in turn be epistatic to l(3)mbt repression in larval brains.…”
Section: The Deletion Of Mmb Components or L(3)mbt Have Overlappingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that the GFP::Piwi protein observed in mip130 1-36 salivary glands is cytoplasmic, whereas native piwi requires translocation into the nucleus to be functional (46), suggesting that the observed expression is not coordinately controlled with other genes required for piwi transport to the nucleus and function in that compartment. Janic et al (11) reported that piwi and other germ-line genes generally repressed in somatic tissues are activated in malignant brain tumor tissue in l(3)mbt mutants. We asked if mip130 1-36 mutation would in turn be epistatic to l(3)mbt repression in larval brains.…”
Section: The Deletion Of Mmb Components or L(3)mbt Have Overlappingmentioning
confidence: 99%
“…The positions, which included piwi, gave a wide coverage range of variation for which siRNA depletion of MMB members affected gene expression and a control with no effect on dramatic derepression (Fig. 6B) (10,11,13,38). FISH polytene barcoding with IHC demonstrated that Mip120, Mip130, and L(3)mbt all occupied the piwi gene position in wild-type salivary glands (Fig.…”
Section: The Deletion Of Mmb Components or L(3)mbt Have Overlappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The untimely expression of gametogenic genes, which has been found to occur in tumors in humans 12,13 and to induce tumorigenesis in Drosophila 14 , might be linked to aneuploidy observed in cancer cells. However, the link between chromosome segregation defects and misregulation of gametogenic genes, including meiotic genes, has not been directly tested.…”
mentioning
confidence: 99%
“…Other methylation changes induced by temozolomide such as N 7 -methylguanine and N 3 -methyladenine are repaired by the base excision repair pathway and are not cytotoxic since temozolomide-induced injury can be repaired by the DNA repair enzymes, including methylguanyl methyltransferase (MGMT). The silencing of the MGMT gene promoter by methylation is associated with better tumor response to combination treatment with radiation and temozolomide [2] Germ cells share several characteristics with cancer cells such as their ability to proliferate, lack of senescence and their undifferentiated state [3]. Antitumoral treatment by temozolomide may result in an altered epigenetic profile in the germline resulting in infertility.…”
Section: Introductionmentioning
confidence: 99%